Multimodal Imaging for the Diagnosis of Accessory Mitral Valve Tissue - Christian Byskov Nielsen; Bjarne Linde Nørgaard; Jesper Møller Jensen; Steen Hvitfeldt Poulsen; Morten Steen Kvistholm Jensen; Mariann Tang; Brian Bridal Løgstrup (Annals of Internal Medicine: Clinical Cases)
Accessory mitral valve tissue (AMVT) is a rare congenital cardiac anomaly often diagnosed in childhood and is associated with left ventricular outflow tract obstruction. We present a case of an asymptomatic adult man in his 60s with an incidental finding of AMVT. A transthoracic echocardiography and transesophageal echocardiography initially raised suspicion of AMVT, but the precise origin of the anomaly was established using a dynamic 4-dimensional cardiac computed tomography scan, ultimately confirming the diagnosis. This case highlights the potential value of multimodality imaging in the diagnosis of AMVT and rules out other differential diagnoses.